Profil ACR-EULAR 2010 Pasien Poliklinik Reumatologi IRJ RSUD DR.Soetomo Surabaya Tahun 2018 - SUKACITA TEHUPURING; ARYATI; LITA DIAH RAHMAWATI (HANG TUAH MEDICAL JOURNAL, 2022)
Background: The 2010 ACR-EULAR criteria were established for the purpose of early diagnosis of Rheumatoid Arthritis (RA). It is hoped that the results of this study can provide evidence of RA patient profile data that can be used nationally to describe medical developments related to RA. The selected profiles are clinical and laboratory profiles to represent morbidity, prognosis, and disease course. Adult patients were selected to represent the socioeconomic impact and RSUD Dr. Soetomo was chosen as a data source to be able to represent RA cases in Eastern Indonesia. Objective: To determine the clinical and laboratory profile of RA patients based on the ACR-EULAR 20210 criteria at Rheumatology Outpatient Installation of RSUD Dr. Soetomo in 2018. Methods: Retrospective-descriptive research using medical record data of RA patients at RSUD Dr. Soetomo. Results: 100% of patients in this study were women. The highest age distribution was 45-64 years 47.83%, 35-44 years 30.43%, 15-24 years 13.04%, 25-34 years 8.70% with a median of 43 years. As many as 82.61% have high school education and 4.35% have junior high school education and 8.70% have less education. 56.52% of patients live outside Surabaya and 43.44% of patients live within the city of Surabaya. 52.17% of patients affected with RA symptoms in 4–10 small joints, 13.04% patients affected more than 10 joints (at least 1 small joint) and 17.39% patients affected 2–10 large joints and 1–3 small joints. 95.65% of patients had pain for 6 weeks or more and only 4.35% of patients had pain for less than 6 weeks. 65.22% of patients showed positive RF serology. 91.30% of patients were anti-MCV positive. 95.65% of patients had an ESR above the normal range with a median of 55 mm/hour. 30.34% of patients showed CRP above the normal limit, 26.09% of patients with CRP within normal limits, while 43,48% of patients had no data on CRP examination results. Evaluation based on the 2010 ACR-EULAR criteria showed 43.48% of patients with a score of 8; 26.09% of patients with a score of 6; 4.35% of patients with a score of 7; and, 13.04% of patients with a score of 9 and with a score of 10. Conclusion: Rheumatoid Arthritis Patients at Rheumatology Outpatient Installation of RSUD Dr. Soetomo Surabaya in 2018 had a demographic profile of more than 45 years old, with a high school education level, came from outside the city of Surabaya and all of them were female; with a clinical profile having involvement of 4–10 joints with a duration of pain more than 6 weeks; has a laboratory profile where most of the RF and Anti-MCV serological results are positive, with an above-normal ESR count in most of the samples; and has a 2010 ACR-EULAR profile at a score of 8 with the largest number of samples and at a score of 7 with the smallest number of samples. Keywords: Rheumatoid Arthritis, ACR-EULAR 2010, RSUD Dr. Soetomo